2020
DOI: 10.1038/s41598-020-71657-9
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the preservation of organic compounds in Mars analog nontronites after exposure to acid and alkaline fluids

Abstract: The presence of organic matter in lacustrine mudstone sediments at Gale crater was revealed by the Mars Science Laboratory Curiosity rover, which also identified smectite clay minerals. Analogue experiments on phyllosilicates formed under low temperature aqueous conditons have illustrated that these are excellent reservoirs to host organic compounds against the harsh surface conditions of Mars. Here, we evaluate whether the capacity of smectites to preserve organic compounds can be influenced by a short exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…Phyllosilicate-bearing layers are desirable targets for investigation on Mars given their potential to enhance the preservation of organics [13][14][15][16][17][18] and serve as indicators of wetter surficial conditions in the past [2,4,10,13,[19][20][21][22][23][24][25]. To investigate the phyllosilicates in Gale crater, drilled rock powders and scooped samples of loose sediment are measured by the Chemistry and Mineralogy (CheMin) X-ray diffractometer.…”
Section: Introductionmentioning
confidence: 99%
“…Phyllosilicate-bearing layers are desirable targets for investigation on Mars given their potential to enhance the preservation of organics [13][14][15][16][17][18] and serve as indicators of wetter surficial conditions in the past [2,4,10,13,[19][20][21][22][23][24][25]. To investigate the phyllosilicates in Gale crater, drilled rock powders and scooped samples of loose sediment are measured by the Chemistry and Mineralogy (CheMin) X-ray diffractometer.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to determine the type of molecule adsorbed in the interlayers with Raman setups of laser spot size larger than the grain size of the minerals analyzed. However, from our previous works centered on the study of clay minerals, we know that its combination with IR spectroscopy can give satisfactory results 15 , 61 , providing the Raman technique powerful information on the surface state and the IR on the molecules adhered in the interlayer.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory studies have also shown that organic molecules (e.g., tholins, chondritic organics) are transformed in aqueous alteration experiments (Kebukawa et al 2013(Kebukawa et al , 2020Brassé et al 2017;Vinogradoff et al 2018;Danger et al 2021), producing numerous new soluble molecules and insoluble OM as a function of time and temperature. The nature and extent of OM evolution likely depends on the nature of the initial molecules, the interaction with minerals, and the fluid properties (Gil-Lozano et al 2020;Haas et al 2020;Vinogradoff et al 2020). The spatial co-occurrence of OM with phyllosilicates and carbonates observed at the surface of Ceres (Raponi et al 2017;De Sanctis et al 2019) suggests a close genetic relationship between these phases and a possible coevolution during hydrothermal processing.…”
Section: Chemical Evolution Of Water-rich Worldsmentioning
confidence: 99%